Clinical Effects and Differences in Neural Function Connectivity Revealed by MRI in Subacute Hemispheric and Brainstem Infarction Patients With Dysphagia After Swallowing Therapy - Huang, Yu-Chi; Hsu, Tun-Wei; Leong, Chau-Peng; Hsieh, Han-Chin; Lin, Wei-Che (Frontiers in Neuroscience, 2018)
Background. Early detection and intervention for post-stroke dysphagia could reduce the incidence of pulmonary complications and mortality. The aims of this study were to investigate the benefits of swallowing therapy in swallowing function and brain neuro-plasticity and to explore the relationship between swallowing function recovery and neuroplasticity after swallowing therapy in cerebral and brainstem stroke patients with dysphagia. Methods. We collected 17 subacute stroke patients with dysphagia (11 cerebral stroke patients with a median age of 76 years and 6 brainstem stroke patients with a median age of 70 years). Each patient received swallowing therapies during hospitalization. For each patient, functional oral intake scale (FOIS), functional dysphagia scale (FDS) and 8-point penetration-aspiration scale (PAS) in videofluoroscopy swallowing study (VFSS), and brain functional magnetic resonance imaging (fMRI) were evaluated before and after treatment. Results. FOIS (p=0.003 in hemispheric group and p=0.039 in brainstem group) and FDS (p=0.006 in hemispheric group and p=0.028 in brainstem group) were both significantly improved after treatment in hemispheric and brainstem stroke patients. In hemispheric stroke patients, changes in FOIS were related to changes of functional brain connectivity in the ventral default mode network (vDMN) of the precuneus in brain functional MRI (fMRI). In brainstem stroke patients, changes in FOIS were related to changes of functional brain connectivity in the left sensorimotor network (LSMN) of the left postcentral region characterized by brain fMRI. Conclusion. Both hemispheric and brainstem stroke patients with different swallowing difficulties showed improvements after swallowing training. For these two dysphagic stroke groups with corresponding etiologies, swallowing therapy could contribute to different functional neuroplasticity.